FOREIGN LANGUAGE AS A KEY FACTOR FOR ACADEMIC MOBILITY OF FUTURE ENGINEER-TEACHERS - Tupchenko V., V.; Pasichnyk , M. (Problems of Engineer-Pedagogical Education, 2024)
Ukraine's intensive integration into the world and European educational community, as well as ensuring the implementation of the Bologna Declaration's key principles - adaptation to the European educational standards, mobility, and professional competition, actualizes current trends to improve and enhance the quality of foreign language education in Ukrainian higher engineering educational institutions, develop appropriate professional and everyday communication skills in future engineer- teachers, and provide scientific and methodological support from academic staff. The purpose of the article is to identify the role of foreign language teaching at higher engineering educational institutions in the context of future engineer-teachers' academic mobility, to define the skills and strategies which are the focus of English communicative course for academic and professional purposes. Based on the analysis of practical experience in teaching English communicative course for academic and professional purposes, the article deals with the skills and strategies which are in the focus of the above-mentioned course; the advantages of teaching an academic English, providing satisfaction of professional and educational needs of future engineers-teachers, development of academic mobility and increasing students' motivation to participate in the international projects. The authors highlight some challenges arising during the integration of the course into the educational process and outline certain requirements for a foreign language teacher and the organizational process. The paper defines the goals and objectives of foreign language training and organizational forms of teaching foreign languages to support students' academic mobility at a higher engineering education institution; emphasizes the importance of creating specialized courses aimed at facilitating students' adaptation to the academic process abroad. The authors propose to correct the goals and update the courses of foreign language training for students at higher engineering educational institutions, reorienting them from mastering all types of speech activities to the development of a secondary linguistic personality; to make corrections to the content of foreign language education - to supplement the existing knowledge system of national and cultural specifics and realities of the English speaking country and to clarify the areas of communicative activity - topics and communicative situations with programs for their deployment.